2014
DOI: 10.1108/compel-05-2013-0192
|View full text |Cite
|
Sign up to set email alerts
|

Radial output space mapping for electromechanical systems design

Abstract: International audiencePurpose – The purpose of this paper is to set a relation through adaptive multi-level optimization between two physical models with different accuracies; a fast coarse model and a fine time consuming model. The use case is the optimization of a permanent magnet axial flux electrical machine. Design/methodology/approach – The paper opted to set the relation between the two models through radial basis function (RBF). The optimization is held on the coarse model. The deduced solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…The parameter that controls the level of accuracy/fidelity-the mesh size in the case of a PDE solver-is one of the inputs of this black box, alongside others such as design or control variables and environmental variables (see, e.g., Santner et al, 2003). Examples of multi-fidelity simulators can be found in virtually all areas of engineering and science, including aeronautics , fire safety (Demeyer et al, 2017), electromechanics (Hage Hassan et al, 2014), electromagnetism (Koziel et al, 2013), haemodynamics (Perdikaris and Karniadakis, 2016) and many more.…”
Section: Introductionmentioning
confidence: 99%
“…The parameter that controls the level of accuracy/fidelity-the mesh size in the case of a PDE solver-is one of the inputs of this black box, alongside others such as design or control variables and environmental variables (see, e.g., Santner et al, 2003). Examples of multi-fidelity simulators can be found in virtually all areas of engineering and science, including aeronautics , fire safety (Demeyer et al, 2017), electromechanics (Hage Hassan et al, 2014), electromagnetism (Koziel et al, 2013), haemodynamics (Perdikaris and Karniadakis, 2016) and many more.…”
Section: Introductionmentioning
confidence: 99%
“…In such applications, it is clearly demonstrated that the powertrain losses must be reduced for low power and low speed in order to increase the vehicle's autonomy [19]. For instance, to assess vehicles powertrain efficiency, a realistic average driving cycle such as ARTEMIS is used [20]. There are various ways of enhancing a power converter's efficiency: these include using new components [6], more complex topologies enabling soft-switching [21], or modular design [22,23], new designs with better integration [24], system considerations and innovative control procedures, e.g.…”
Section: Introductionmentioning
confidence: 99%